Hubungan Pengetahuan Keluarga Terhadap Pengendalian Kadar Glukosa Darah Penderita Diabetes Melitus - Napitupulu, Mastiur; ., Sutriningsih (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Diabetes mellitus is a chronic disease whose prevalence rate is increasing every year which, if not managed properly, can cause various chronic complications, such as cerebrovascular disease, coronary heart disease, and others. Family knowledge is one of the treatments to control blood sugar levels of patients with diabetes mellitus. The purpose of this study was to determine the relationship between family knowledge and control of blood glucose levels in patients with diabetes mellitus in the work area of Pokenjior Health Center in 2019. This research uses descriptive descriptive design with cross sectional approach. The sampling technique in this study was a total sampling of 50 respondents.The results of the study through the Kolmogorov-smirnov test, obtained a p-value of 0.013 (<0.05) meaning that there is a significant relationship between family knowledge and controlling blood glucose levels of patients with diabetes melitus. The results of this study recommend that families with diabetes melitus obtain good knowledge to control their blood glucose levels.